A Tetra-PEG Hydrogel Based Aspirin Sustained Release System Exerts Beneficial Effects on Periodontal Ligament Stem Cells Mediated Bone Regeneration - Zhang, Yunfan; Ding, Ning; Zhang, Ting; Sun, Qiannan; Han, Bing; Yu, Tingting (Frontiers in Chemistry, 2019)
Bone defects, massive bone defects in particular, is still an issue clinically. Acetylsalicylic acid (ASA), also known as aspirin, has been proven to be conducive for mesenchymal stem cells osteogenic differentiation, which may be benefited for bone regeneration. In order to achieve a more appealing prognosis of bone defect, here we develop a well-defined tetra-PEG hydrogel sealant with rapid gelation speed, strong tissue adhesion, and high mechanical strength. After in-situ encapsulation of aspirin, this drug-loaded tetra-PEG hydrogel possessed a sustained release, anti-inflammation, and osteoinductive properties. In vitro experiments showed that the cell proliferation was slightly facilitated, and the osteogenic differentiation was notably augmented when periodontal ligament stem cells (PDLSCs) were co-incubating with the hydrogel materials. Moreover, in vivo study manifested that the aspirin sustained release system significantly facilitated the PDLSCs mediated bone defect regeneration. Overall, tetra-PEG hydrogel-based aspirin sustained release system is applicable not only for enhancing the osteogenesis capacity of PDLSC but also providing a new thought of bone regenerative therapy.